Pengembangan Lms Berbasis Moodle Menggunakan Model Project Based Learning Untuk Meningkatkan Keterampilan Kreativitas Murid Kelas X Materi C++ - Dicky Andi Soffan; Atan Pramana (CV. SINAR HOWUHOWU, 2026)
Technology-based learning is one of the important needs to support the development of students' creativity skills in facing the demands of 21st-century learning, especially in programming subjects. However, C++ learning in class X SMK Sejahtera Surabaya is still dominated by conventional methods so that students' creativity in exploring ideas, solving problems, and developing programming projects is not optimal, and the utilization of the Learning Management System (LMS) does not support project-based learning optimally. This study aims to develop a Moodle-based LMS using a feasible and effective Project Based Learning (PjBL) model to improve students' creativity skills in C++ material. The study used the Research and Development (R&D) method with the ADDIE model which includes learning needs analysis, LMS and learning tool design, product development and validation, implementation in class X TKJ students of SMK Sejahtera Surabaya, and evaluation of product feasibility and effectiveness. The results showed media validation of 80%, learning tools 88%, materials 87%, and questions 86%. The average posttest score of the experimental class was 81.6, higher than the control class's score of 69.8, with the Mann–Whitney U test obtaining a significance value of 0.002 (p< 0.05). This finding implies that a Moodle-based LMS integrated with PjBL can be an alternative learning medium that supports increasing student creativity in C++ programming learning.